Aldose Reductase: An Emerging Target for Development of Interventions for Diabetic Cardiovascular Complications - Jannapureddy, Sravya; Sharma, Mira; Yepuri, Gautham; Schmidt, Ann Marie; Ramasamy, Ravichandran (Frontiers in Endocrinology, 2021)
Diabetes is a leading cause of cardiovascular morbidity and mortality. Despite numerous treatments for cardiovascular disease (CVD), for patients with diabetes, these therapies provide less benefit for protection from CVD. These considerations spur the concept that diabetes-specific, disease-modifying therapies are essential to identify, especially as diabetes epidemic continue to expand. In this context, high levels of blood glucose stimulate the flux via aldose reductase (AR) pathway leading to metabolic and signaling changes in cells of the cardiovascular system. In animal models flux via AR in hearts is increased by ischemia and its inhibition during ischemia reperfusion reduces injury. In mice models of diabetic atherosclerosis, human AR expression accelerates progression and impairs regression of atherosclerotic plaques. Genetic studies have revealed that single nucleotide polymorphisms (SNPs) of the ALD2 (human AR gene) is associated with diabetic complications, including cardiorenal complications. This Review presents current knowledge regarding the roles for AR in the causes and consequences of diabetic cardiovascular disease and the status of AR inhibitors in clinical trials. Studies from both human subjects and animal models are presented to highlight the breadth of evidence linking AR to the cardiovascular consequences of diabetes.